Abnormal passive chloride absorption in cystic fibrosis jejunum functionally opposes the classic chloride secretory defect - Russo, Michael A. (American Society for Clinical Investigation, 2003)
Due to genetic defects in apical membrane chloride channels, the cystic fibrosis (CF) intestine does not secrete chloride normally. Depressed chloride secretion leaves CF intestinal absorptive processes unopposed, which results in net fluid hyperabsorption, dehydration of intestinal contents, and a propensity to inspissated intestinal obstruction. This theory is based primarily on in vitro studies of jejunal mucosa. To determine if CF patients actually hyperabsorb fluid in vivo, we measured electrolyte and water absorption during steady-state perfusion of the jejunum. As expected, chloride secretion was abnormally low in CF, but surprisingly, there was no net hyperabsorption of sodium or water during perfusion of a balanced electrolyte solution. This suggested that fluid absorption processes are reduced in CF jejunum, and further studies revealed that this was due to a marked depression of passive chloride absorption. Although Na(+)-glucose cotransport was normal in the CF jejunum, absence of passive chloride absorption completely blocked glucose-stimulated net sodium absorption and reduced glucose-stimulated water absorption 66%. This chloride absorptive abnormality acts in physiological opposition to the classic chloride secretory defect in the CF intestine. By increasing the fluidity of intraluminal contents, absence of passive chloride absorption may reduce the incidence and severity of intestinal disease in patients with CF.